Enhancing Students’ Pollution Problem-Solving Skills Through Problem-Based Learning: The Moderating Role of Mathematical Literacy - Indri Yani; Sandi Budiana; Teti Rostikawati; Fitri Siti Sundari; M. Afifuddin Khotibul Umam (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study examines the effectiveness of the Problem-Based Learning (PBL) model in enhancing university students’ ability to solve environmental pollution problems, with mathematical literacy as a moderating variable. Conducted in Indonesia, the research adopted a quasi-experimental non-equivalent pretest-posttest control group design involving 64 biology education students from Universitas Pakuan. Participants were assessed using open-ended problem-solving tests and a rubric aligned with the PISA framework. Results from two-way ANOVA showed significant effects of the learning model (F(1, 58) = 32.84, p < .001, η² = .216) and mathematical literacy levels (F(2, 58) = 29.17, p < .001, η² = .201) on problem-solving performance. Although both groups improved by 18.75 points from the pretest to the post-test, the PBL group outperformed the control. Post hoc analysis (Tukey HSD) revealed that students with high mathematical literacy achieved the highest scores (M = 91.8, SD = 3.7), confirming its moderating effect. These findings underscore the value of integrating mathematical literacy into PBL to promote contextual learning and real-world problem-solving. Future studies should explore broader samples and longitudinal impacts across diverse educational contexts.